Inhalation Exposure Analysis of Lung-Inhalable Particles in an Approximate Rat Central Airway - Dong, Jingliang (Int J Environ Res Public Health, 2019)
Rats have been widely used as surrogates for evaluating the adverse health effects of inhaled airborne particulate matter. This paper presents a computational fluid and particle dynamics (CFPD) study of particle transport and deposition in an approximate rat central airway model. The geometric model was constructed based on magnetic resonance (MR) imaging data sourced from previous study. Lung-inhalable particles covering a diameter range from 20 nm to 1.0 µm were passively released into the trachea, and the Lagrangian particle tracking approach was used to predict individual particle trajectories. Overall, regional and local deposition patterns in the central airway were analyzed in detail. A preliminary interspecies data comparison was made between present rat models and previously published human data. Results showed deposition “hot spots” were mainly concentrated at airway bifurcation apexes, and a gravitational effect should also be considered for inertia particles when using a rat as a laboratory animal. While for humans, this may not happen as the standing posture is completely different. Lastly, the preliminary interspecies data comparison confirms the deposition similarity in terms of deposition enhancement factors, which is a weighted deposition concentration parameter. This interspecies comparison confirms feasibility of extrapolating surrogate rat deposition data to humans using existing data extrapolation approach, which mostly relies on bulk anatomical differences as dose adjustment factors.